Gender differences in aphasia outcomes: evidence from the AphasiaBank. Issue 5 (30th June 2019) - Sharma, Saryu; Briley, Patrick M.; Wright, Heather Harris; Perry, Jamie L.; Fang, Xiangming; Ellis, Charles
Abstract: Background: Stroke is one of the leading causes of death in the United States. Aphasia is a language impairment which results as a consequence of stroke. Gender differences are reported in underlying mechanisms of stroke, however, gender differences in aphasia type and severity remain unclear. Aims: To examine gender differences in aphasia impairment based on data from AphasiaBank, a research repository of data obtained from studies of aphasia. Methods & Procedures: The data were collected from AphasiaBank for 294 persons with aphasia (PWA) (172 men, 122 women). Baseline comparisons by gender groups were completed using independent samples t ‐tests and Pearson Chi square statistics. Univariate comparisons of the total Western Aphasia Battery—Revised (WAB‐R) ‐AQ and ‐R subtests' scores were compared between the two groups using independent samples t ‐tests. Multivariate comparisons were completed by using multivariate analysis of variance (MANOVA). Outcomes & Results: Gender differences were observed in the severity of aphasia with men exhibiting more severe aphasia than women. Analyses of WAB‐R indicated greater impairment among men based on AQ and greater impairment was observed in individual subtest performance. Men exhibited statistically significantly lower WAB‐R AQs than women (67.4 versus 75.6). Lower WAB‐R AQs were derived from lower scores among men on individual subtests; information content, fluency, repetition, sentence completion, responsive speech and tests of comprehension (yes/no, auditory word recognition and sequential commands). Conclusions & Implications: This study offers evidence of gender differences in aphasia severity, global communication impairment and lower scores on individual subtests used to derive the WAB‐R AQ. The limitations of the study with suggestions for future directions are presented.